(untitled) (Herald of Journalism, 2018)
The article examines the impact of new media on the public consciousness, all sorts of shapes and styles of expression, socialization and management, which allow to achieve better results in the impact on the public consciousness, as well as the manipulation of the mass consciouslution and links it to the unprecedented the development of media and their pervasive influence on public life.